Improving distance learning mathematics modules in South Africa: A learning design perspective - Greyling, L.E.; Huntley, B.; Reedy, K.; Rogaten, J. (South African Journal of Higher Education, 2020)
In order to deliver high-quality learning and teaching, the Open University (OU) has adopted an approach to developing its curriculum called OU Learning Design, which supports a consistent and structured design, specification and review process. It provides a simple set of tools and resources to assist teams in choosing and integrating an effective range of media and technologies, defining their pedagogic approach, and sharing good practice across the institution (Subotzky and Prinsloo 2011). The objective of this study was to apply OU Learning Design tools in the context of the largest distance education university in Africa (Unisa) to identify areas that could be changed in order to improve student outcomes and retention. Two Unisa first-level mathematics modules were evaluated and mapped using OU Learning Design approaches and tools to identify areas for improvement. Qualitative and quantitative data on students’ educational experience in these modules and longitudinal academic progress data were used to better understand the challenges students are facing on those courses. The process uncovered areas where improvements need to be made and among the core recommendations were improvement of workload distribution across both modules, the timing of the examination period, and a greater variety of learning activities. These reflections will be used to inform the next “Plan” stage of the Action Research spiral.